Efficient recycling of spent Li-ion battery cathodes by laser-induced high-temperature thermal shock - Ning Cao; Yang Zhang; Xin Gu; Mingbo Wu (Nature Communications)
Abstract Environmental concerns over heavy metals in spent lithium-ion batteries (LIBs), coupled with the growing scarcity of metal resources, have heightened the need for efficient and cost-effective recycling of metals from spent cathodes. In this study, we propose a laser-induced high-temperature thermal shock strategy that rapidly separates cathode materials from Al foil in just seconds. The instantaneous thermal shock facilitates the reduction of refractory metal oxides and the decomposition of impurity layer, while simultaneously increasing the specific surface area and generating oxygen vacancies. This significantly enhances both the thermodynamics and kinetics of the subsequent leaching process. Leaching tests with 0.1 M HCl show that the efficiencies for Co, Ni, and Mn increase by 147.5%, 125.6%, and 140.0%, respectively, compared to untreated materials. Over 97% of the metals are recovered even using 0.5 M HCl. Here, we propose a laser strategy that is more economically viable and significantly reduces the environmental impact.